Inter and intraplane softening of the vortex structure: a two-step transition - Yazyi, Jorge Omar; Arribére, Abel Alberto; Durán, C.; de la Cruz, F.; Mitzi, D. B.; Kapitulnik, A. (Comisión Nacional de Energía Atómica; Argentina, 1991)
Fil: Yazyi, Jorge Omar. Comisión Nacional de Energía Atómica; Argentina